Average Error: 0.0 → 0.0
Time: 16.8s
Precision: 64
\[{\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x\]
\[{\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x\]
{\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x
{\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x
double f(double x) {
        double r1463284 = x;
        double r1463285 = sqrt(r1463284);
        double r1463286 = log(r1463284);
        double r1463287 = r1463285 + r1463286;
        double r1463288 = sqrt(r1463287);
        double r1463289 = 2.0;
        double r1463290 = pow(r1463288, r1463289);
        double r1463291 = r1463290 - r1463284;
        return r1463291;
}

double f(double x) {
        double r1463292 = x;
        double r1463293 = sqrt(r1463292);
        double r1463294 = log(r1463292);
        double r1463295 = r1463293 + r1463294;
        double r1463296 = sqrt(r1463295);
        double r1463297 = 2.0;
        double r1463298 = pow(r1463296, r1463297);
        double r1463299 = r1463298 - r1463292;
        return r1463299;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[{\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x\]
  2. Final simplification0.0

    \[\leadsto {\left(\sqrt{\sqrt{x} + \log x}\right)}^{2} - x\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "pow(sqrt(sqrt(x)+log(x)),2) - x"
  :precision binary64
  (- (pow (sqrt (+ (sqrt x) (log x))) 2) x))